Feasibility of Algae Photobioreactor as Façade in the Office Building in Indonesia. (August 2019) - Ardiani, N A; Koerniawan, M D; Martokusumo, W; Suyono, E A; Poerbo, H W
Abstract: Algae has a high potential as a renewable energy resource. Recent studies about algae photobioreactor application in the building façade seem promising and the first algae building has been constructed in Hamburg, Germany. However, the application of algae photobioreactor in the hot and humid climate is still limited. This paper will discuss the feasibility of algae photobioreactor as façade in the office building by evaluating the model from Sketchup software. This is a real project of a new office building, named ITB Innovation Park at Institut Teknologi Bandung campus, Jalan Ganesha no. 15. The algae photobioreactor is planned to be installed in the west façade as shading devices and renewable energy resources. It is assumed that the acrylic moulding would work better to reduce leakage issues and the possibility of killing the algae.